Penelitian Etnografi dalam Pendidikan - Nidia Lutfianti; Meyniar Albina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores ethnographic research methods in education, focusing on their characteristics, types, advantages, and limitations. The study aims to provide a systematic understanding of ethnographic research in education and identify steps to enhance its validity and reliability. A library research approach was used, analyzing various academic sources. The findings reveal that ethnography provides deep insights into school culture, classroom social interactions, and student-teacher communication patterns. Identified types of ethnographic research include realist, critical, and case study ethnography. While this method offers a holistic understanding of educational contexts, it also has drawbacks, such as researcher subjectivity and extended time requirements.